(untitled) - Adler, Ronald B. (NewYork, 2005)
This text, in business communication, takes a pragmatic approach that features a strong multicultural focus, a heavy emphasis on effective presentations and a teaching programme that is designed to encourage group activities and skill building.
Keywords: Business communication,Interpersonal communication,Giao tiếp trong kinh doanh,Giao tiếp giữa người với người